Coding at a Crossroads. - RESNICK, MITCHEL; RUSK, NATALIE (Communications of the ACM, 2020)
The article discusses computer coding education, particularly focusing upon the need for the development of values, pedagogies and educational strategies that benefit students. It discusses the use of programming interfaces such as Scratch, student motivation as it relates to coding, and presents four guiding principles of creative learning.